Transformasi Pendidikan di Pesantren Abad 21 - Sri Andri Astuti (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2019)
This paper to describe the changes in pesantren in the face of globalization. Globalization is one of the challenges for pesantren. Pesantren is facing globalization to move towards a more advanced future. Pesantren always improve quality and quality to face globalization. Pesantren always improve quality and quality to face globalization. The steps that must be undertaken by pesantren are to remain as an educational institution for cadre scholars by adjusting the demands of modernization and globalization, as a center for the development of special knowledge of Islamic religion, and placing itself as a transformation, motivator and innovator. For that pesantren must make changes by means of modification and improvisation including; Improving the curriculum through comprehensive education planning; Changes in pesantren infrastructure and physical buildings; Pattern of management and management of pesantren; Changes in the widening scope and level of education in pesantren; How to behave in a pesantren that is no longer closed; and Support of a positive attitude from the government